Cyanoacetylenic Alcohols: Molecules of Interstellar Relevance in the Synthesis of Essential Heterocycles, Amino Acids, Nucleobases and Nucleosides - Trofimov, Boris A.; Mal’kina, Anastasiya G. (Synthesis, 2021)
Cyanoacetylenic alcohols, R1R2C(OH)C≡C–CN, the closest derivatives of cyanoacetylene, an abundant interstellar molecule, are now becoming important compounds in the area of modern organic synthesis that tends to mimic Nature. The presence of highly reactive C≡C and C≡N bonds in close proximity to a hydroxy group endows cyanoacetylenic alcohols with a chemical trinity of mutually influencing functions, leading to a myriad number of chemical transformations. All reactions of cyanoacetylenic alcohols parallel modern organic synthesis, whilst being biomimetic. To react, they do not need transition metals (and in most cases, no metals at all, except for physiologically indispensable Na+ and K+), proceed at ambient temperature and often in aqueous media. Fundamentally, their reactions are 100% atom-economic because they are almost exclusively addition processes. Typically, the cyano, acetylene and hydroxy functions of cyanoacetylenic alcohols behave as an inseparable entity, leading to reaction products with multiple functional groups. This allows hydroxy, carbonyl, carboxylic, imino, amino, amido, cyanoamido, cyano, various P-containing, ether and ester functions, along with double bonds, different fundamental heterocycles (furans, furanones, pyrazoles, oxazoles, pyridines, pyrimidines, purines, etc.) and diverse polycyclic systems to be integrated in a single molecular architecture. This review focuses on an analysis and generalization of the knowledge that has accumulated on the chemistry of cyanoacetylenic alcohols, mostly over the past 15 years.1 Introduction2 Nucleophilic Addition to Cyanoacetylenic Alcohols and Subsequent Transformations of the Adducts3 Annulation with Nonaromatic Nitrogen Heterocycles4 Annulation with Aromatic Nitrogen Heterocycles5 Modification of Amino Acids6 Modifications of Nucleobases7 Modification of Nucleosides8 Conclusion
Keywords: cyanoacetylenic alcohols; nucleophilic addition; annulation; modification; fundamental heterocycles